210k views
0 votes
7y=3x−7 Complete the missing value in the solution to the equation. (1, )

User Lbusett
by
5.5k points

2 Answers

6 votes


\bf 7y=3x-7~\hspace{5em}(\stackrel{x}{1},\stackrel{y}{\phantom{X}})~\hspace{5em} \stackrel{x = 1}{7y=3(1)-7} \\\\\\ 7y=-4\implies y=\cfrac{-4}{7} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill \left(\stackrel{x}{1},\stackrel{y}{-(4)/(7)}\right)~\hfill

User Joseline
by
5.5k points
3 votes
plug 1 in for x to get 7y=3(1)-7

7y=-4
y=-4/7
User Yagnik Detroja
by
6.6k points